Conventional dendritic cells type 1 are strongly enriched, quiescent and relatively tolerogenic in local inflammatory arthritis - Arjan Boltjes; Anoushka Ashok Kumar Samat; Maud Plantinga; Michal Mokry; Bas Castelijns; Joost F. Swart; Sebastiaan J. Vastert; Sebastiaan J. Vastert; Menno Creyghton; Menno Creyghton; Stefan Nierkens; Stefan Nierkens; et al. (Frontiers in Immunology, 2023)
IntroductionDendritic cells (DC) are crucial for initiating and shaping immune responses. So far, little is known about the functional specialization of human DC subsets in (local) inflammatory conditions. We profiled conventional (c)DC1, cDC2 and monocytes based on phenotype, transcriptome and function from a local inflammatory site, namely synovial fluid (SF) from patients suffering from a chronic inflammatory condition, Juvenile Idiopathic Arthritis (JIA) as well as patients with rheumatoid arthritis (RA).MethodsPaired PB and SF samples from 32 JIA and 4 RA patients were collected for mononuclear cell isolation. Flow cytometry was done for definition of antigen presenting cell (APC) subsets. Cell sorting was done on the FACSAria II or III. RNA sequencing was done on SF APC subsets. Proliferation assays were done on co-cultures after CD3 magnetic activated cell sorting (MACS). APC Toll-like receptor (TLR) stimulation was done using Pam3CSK4, Poly(I:C), LPS, CpG-A and R848. Cytokine production was measured by Luminex.ResultscDC1, a relatively small DC subset in blood, are strongly enriched in SF, and showed a quiescent immune signature without a clear inflammatory profile, low expression of pathogen recognition receptors (PRRs), chemokine and cytokine receptors, and poor induction of T cell proliferation and cytokine production, but selective production of IFNλ upon polyinosinic:polycytidylic acid exposure. In stark contrast, cDC2 and monocytes from the same environment, showed a pro-inflammatory transcriptional profile, high levels of (spontaneous) pro-inflammatory cytokine production, and strong induction of T cell proliferation and cytokine production, including IL-17. Although the cDC2 and monocytes showed an overlapping transcriptional core profile, there were clear differences in the transcriptional landscape and functional features, indicating that these cell types retain their lineage identity in chronic inflammatory conditions.DiscussionOur findings suggest that at the site of inflammation, there is specific functional programming of human DCs, especially cDC2. In contrast, the enriched cDC1 remain relatively quiescent and seemingly unchanged under inflammatory conditions, pointing to a potentially more regulatory role.